The Double Bind of Communicating About Zoonotic Origins: Describing Exotic Animal Sources of COVID‐19 Increases Both Healthy and Discriminatory Avoidance Intentions. Issue 3 (2nd June 2021) - LaCour, Mark; Hughes, Brent; Goldwater, Micah; Ireland, Molly; Worthy, Darrell; Van Allen, Jason; Gaylord, Nick; Van‐Hoosier, Garrett; Davis, Tyler
Abstract: Many novel diseases are of zoonotic origin, likely including COVID‐19. Describing diseases as originating from a diverse range of animals is known to increase risk perceptions and intentions to engage in preventative behaviors. However, it is also possible that communications depicting use of exotic animals as food sources may activate stereotypes of cultures at the origin of a disease, increasing discriminatory behaviors and disease stigma. We used general linear modeling and mediation analysis to test experimental data on communications about zoonotic disease origins from the critical first two months leading up to the declaration of a global pandemic. Results suggest that communications about potential familiar food origins (pigs) affected people's risk perceptions, health behaviors, and COVID‐19 stigma compared to more exotic food sources (e.g., snakes). Participants ( N = 707) who read descriptions of exotic origins viewed the virus as riskier and reported stronger intentions to engage in preventative behaviors than those who read about familiar origins (pigs). However, reading exotic origin descriptions was also associated with stronger intentions to avoid Asian individuals and animal products. These results are critical for both theory and public policy. For theory, they are the first to experimentally demonstrate that zoonotic origin descriptions can impact intentions to engage in discriminatory behaviors for cultures viewed as the origin of a novel infectious disease. For policy, they offer clear, actionable insights on how to communicate about risks associated with a novel zoonosis while managing the potential impact on discriminatory behaviors and stigma.